2005
DOI: 10.1108/13552550510590527
|View full text |Cite
|
Sign up to set email alerts
|

Following the pathway of female entrepreneurs

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 35 publications
6
140
0
10
Order By: Relevance
“…On the other hand, women in developing countries were motivated by a combination of push and pull factors. It is further noted by McClelland et al (2005) that women are increasingly becoming more motivated by the social contribution that their businesses can make to society. Desire for self-fulfillment is an important motivator to start up a business.…”
Section: Internal Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, women in developing countries were motivated by a combination of push and pull factors. It is further noted by McClelland et al (2005) that women are increasingly becoming more motivated by the social contribution that their businesses can make to society. Desire for self-fulfillment is an important motivator to start up a business.…”
Section: Internal Motivationmentioning
confidence: 99%
“…Besides social support, strong ties in the business world do help women in achieving success in their businesses. A study of McClelland et al (2005) showed that the female entrepreneurs in Canada, Singapore and Ireland utilized networking as a means of business development. Other factor such as internal motivation is another important factor that can contribute to success in business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also correlates with their business strategy. According to McClelland et al (2005), business owners are known to be moved by 'pull factors' (inner drive) and 'push factors' (outside forces). The 'pull factors' relate to the entrepreneurs desire for independence, to be one's own boss, to pursue a hobby or natural inclination and express one's own creativity, as well as engage in a passion.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, very small businesses account for a vast proportion of enterprise (seventy three per cent of all UK enterprises have no employees and seventeen per cent of these, are managed solely by women (Harding 2006)). UK female entrepreneurship is a significant economic and social phenomenon and it is increasing (this is true for other countries too (McClelland et al 2005)), especially in rural areas (Harding 2006). Accordingly, U.K. policy makers are aware that female entrepreneurship offers some solution to the problems of the loss to the economy of highly skilled female labour as a result of family formation (The UK Women's Enterprise Task Force was set up in 2005 as a response to this).…”
Section: Further Backgroundmentioning
confidence: 99%
“…Specifically, the paper moves forward debates about entrepreneurship as one option available to professional women who experience, suffer or choose fractured careers as a result of motherhood priorities. The arguments here call for an agenda that takes seriously new, entrepreneurial economic actors who are embedded in domestic spaces, a type of business owner who belongs to a growing and significant phenomenon in countries throughout the world (Harding 2006, McClelland et al 2005.…”
Section: Introductionmentioning
confidence: 99%